Branched-Chain Amino Acid Supplementation Does Not Preserve Lean Mass or Affect Metabolic Profile in Adults with Overweight or Obesity in a Randomized Controlled Weight Loss Intervention. Issue 4 (4th February 2021) - Ooi, Delicia S Q; Ling, Jennifer Q R; Sadananthan, Suresh Anand; Velan, S Sendhil; Ong, Fang Yi; Khoo, Chin Meng; Tai, E Shyong; Henry, Christiani Jeyakumar; Leow, Melvin K S; Khoo, Eric Y H; Tan, Chuen Seng; Lee, Yung Seng; et al.
ABSTRACT: Background: Branched-chain amino acid (BCAA) supplementation has been shown to increase muscle mass or prevent muscle loss during weight loss. Objective: We aimed to investigate the effects of a BCAA-supplemented hypocaloric diet on lean mass preservation and insulin sensitivity. Methods: A total of 132 Chinese adults (63 men and 69 women aged 21–45 y, BMI 25–36 kg/m 2 ) were block randomly assigned by gender and BMI into 3 hypocaloric diet (deficit of 500 kcal/d) groups: standard-protein (14%) with placebo (control, CT) or BCAA supplements at 0.1 g · kg −1 body weight · d −1 (BCAA) or high-protein (27%) with placebo (HP). The subjects underwent 16 wk of dietary intervention with provision of meals and supplements, followed by 8 wk of weight maintenance with provision of supplements only. One-way ANOVA analysis was conducted to analyze the primary (lean mass and insulin sensitivity) and secondary outcomes (anthropometric and metabolic parameters) among the 3 groups. Paired t -test was used to analyze the change in each group. Results: The 3 groups demonstrated similar significant reductions in body weight (7.97%), fat mass (13.8%), and waist circumference (7.27%) after 16 wk of energy deficit. Lean mass loss in BCAA (4.39%) tended to be lower than in CT (5.39%) and higher compared with HP (3.67%) ( P = 0.06). Calf muscle volume increased 3.4% in BCAA and intramyocellular lipids (IMCLs) decreased in BCAA (17%) and HP (18%) ( P < 0.05) over 16 wk. During the 8 wk weight maintenance period, lean mass gain in BCAA (1.03%) tended to be lower compared with CT (1.58%) and higher than in HP (−0.002%) ( P = 0.04). Lean mass gain differed significantly between CT and HP ( P = 0.03). Insulin sensitivity and metabolic profiles did not differ among the groups throughout the study period. Conclusions: BCAA supplementation does not preserve lean mass or affect insulin sensitivity in overweight and obese adults during weight loss. A higher protein diet may be more advantageous for lean mass preservation.